1727. Candida albicans Phosphatidylinositol-(4,5)-Bisphosphate (PIP2) Directs Aberrant Cytokinesis and Septation in Response to Echinocandins, Which Correlates with Fungicidal Activity and Attenuated Virulence - Badrane, Hassan (Open Forum Infect Dis, 2019)
BACKGROUND: We previously showed that highly dynamic PIP2, septin, and PKC-Mkc1 cell wall integrity pathway responses correlate with echinocandin activity against C. albicans and attenuated virulence during invasive candidiasis. Our objectives were to determine whether PIP2 dysregulation in response to an echinocandin results in aberrant localization of the septation and cytokinesis apparatus, and to quantitate aberrant localization. METHODS: Live cell imaging (LCI) was performed for 3 hours (Nikon A1 confocal microscope, NIS Elements software; Tokyo) on C. albicans irs4 mutant and wild-type SC5314 expressing fluorescently labeled PIP2 and Cdc10 (septin), Act1 (actin), or Myo1 (myosin). RESULTS: C. albicans irs4, in which PIP2 5’-phosphatase is disrupted, mislocalizes PIP2 and septins, and over-activates the PKC-Mkc1 pathway in a manner similar to echinocandin-exposed C. albicans SC5314. LCI revealed that PIP2 co-localized with Act1 and Myo1 at aberrant sites in C. albicans irs4, similar to PIP2-Cdc10 co-localization. 83% of co-localizing patches were in cells undergoing active cytokinesis. 78% of patches were at sites of cytokinesis, which reflected both normal budding and abnormal, wide-necked budding; 5% of patches localized to aberrant plasma membrane sites during cytokinesis. 17% of co-localizing patches were in cells that were not undergoing active cytokinesis. 6% of patches were at old cytokinesis sites; 11% of patches were at aberrant plasma membrane sites. Similar PIP2-septin-actin-myosin dysregulation was observed in C. albicans SC5314 immediately upon 4x MIC caspofungin exposure (Figure; videos). CONCLUSION: Dysregulated C. albicans PIP2 recruits the septation and cytokinesis apparatus, including septins, actin, and myosin, to sites of incomplete cytokinesis at bud necks and to sites of aberrant, ectopic septation in plasma membranes of both dividing and non-dividing cells. Our data support a model in which a dysregulated PIP2 response is triggered immediately upon echinocandin exposure, over-activates the PKC-Mkc-1 pathway, and correlates with the extent of fungicidal activity and attenuated virulence. PIP2-septation-cytokinesis dysregulation is likely to lead to C. albicans death by promoting cell lysis, or selecting cells to undergo apoptosis. [Image: see text] DISCLOSURES: All authors: No reported disclosures.